Breaking the Binary: The New Zealand National Party and the framing of the everyday subject - Clifford, Joe (New Zealand Sociology, 2022)
Globally political parties across the ideological spectrum have attempted to frame themselves as representatives of everyday citizens. In both the United Kingdom and the United States, the rise of populist and more openly nationalist politicians on the centre right has been met with an increase in popularity of figures to the left of established members of the Democratic and Labour parties. The rhetoric of these ‘populist’ figures centres on their supposed reclamation of a national people-centred politics from a corrupt elite. Whilst the political discourse of the centre right in New Zealand makes much use of the concept of ‘everydayness’, it is fundamentally different from the popular expressions of the new right in the United States and the United Kingdom. These expressions of the ‘everyday kiwi’ by the National Party are aimed at the confusion of a national politics with a class based one. This allows for the evoking of the ‘everyday’ and ‘kiwi way of life’ to serve an ideological function for those who would use populist lite rhetoric for neoliberal ends. I argue analysis of this type of political style is an under researched area in New Zealand politics and constitutes an increasingly important form of claim making by the National Party.